Mekanisme Pengembalian Kerugian Keuangan Negara Akibat Proyek Gagal - Angga Prayudha; Bisdan Sigalingging (Lembaga Pengembangan Kinerja Dosen, 2024)
Projects run by a company or organization often fail or do not achieve the planned goals, this is not uncommon due to errors in carrying out the project., Regarding the existence of financial losses of the State, in the legal dimension of the State administration is in principle oriented towards the recovery of these losses, and can be applied cumulatively with other sanctions, namely: administrative, criminal and civil witnesses. The purpose of this study is for the Mechanism for Returning State Financial Losses Due to Failed Projects. This type of research is a normative research approach to legislative research (Statute Approach) and through primary data by processing data from primary legal materials, secondary legal materials, and tertiary legal materials. Based on the results of the study, if the settlement of regional loss cases by deliberation for consensus is not reached, then the local government should be able to do other ways in accordance with the provisions stipulated in the Presidential Regulation on Government Procurement of Goods/Services, namely through arbitration, alternative dispute resolution or court in accordance with the provisions of laws and regulations. Alternative dispute resolution is an out-of-court dispute resolution institution through procedures agreed upon by the parties, consisting of negotiation, mediation, conciliation, and expert assessment. Therefore, local governments should seek to recover regional losses by means of asbitrase and alternative dispute resolution first, before handing over the case of regional losses to APH.